Attitudes The King Ghazi Direction British Policy In Iraq 1933-1939 (Journal of the College of Education for Women, 2019)
The period of the reign of King Ghazi saw many disorders in most parts of the country and the management disrupted and imbalanced, besides tribal unrests and political conflict and collision with British interests, Such as bad management in some regions and loss of government control over some administrative units, due to the position of the weak governments towards these problems, so it was necessary to change these Governments and Ministers to solve such problems. In contrast, the Iraqi government has focused on the army as the basis for a strong state and the protector on the existence of an external threat for the safety of the country, King Ghazi has helped in the development of competencies of the military, bringing the officers exercising strong pressure towards reducing Britain's influence in Iraq, That was rejected by Britain, which readying itself to weaken the army by the reduction of arming and instigating internal problems and to stand against the policy of King Ghazi, in the development of the army.The policy of King Ghazi caused concern to the British embassy in Iraq and then the British Government, that the British influence was imposing control in each of the departments of the states and in the army, so the British officials realized that the presence of the king became a threat to their interests, which prompted the British Ambassador (Morris Peterson ) to make a statement publicly when he left Baghdad in March 1939, saying that "the King Ghazi, must be controlled or thrown off."